2020
DOI: 10.1016/j.seizure.2020.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA expression profiles of cerebrospinal fluid in febrile seizure patients

Abstract: Febrile seizures (FS) are the most common seizures found in pediatric patients. Recently, microRNA (miRNA) have been used as a novel biomarker for the diagnosis of various diseases. This study aims to explore the exosomal miRNA expression profile of the cerebrospinal fluid (CSF) in atypical FS patients. Methods: This is a case-control study including CSF specimens of 41 pediatric patients. The CSF specimens were categorized into FS and a control group. Microarray assays were performed to evaluate the CSF exoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Lumbar puncture and cerebrospinal fluid (CSF) analysis are not recommended routinely to evaluate FS patients so was not conducted in the present study. In a recent study, Kim et al 23 searched the miRNA profile of CSF in FS patients. They reported 95 miRNAs were significantly higher in patients than in controls and the top 5 highly expressed miRNAs were miRNA-4486, miRNA-6850-5p, miRNA-642-3p, miRNA-7107-5p and miRNA-4281.…”
Section: Discussionmentioning
confidence: 99%
“…Lumbar puncture and cerebrospinal fluid (CSF) analysis are not recommended routinely to evaluate FS patients so was not conducted in the present study. In a recent study, Kim et al 23 searched the miRNA profile of CSF in FS patients. They reported 95 miRNAs were significantly higher in patients than in controls and the top 5 highly expressed miRNAs were miRNA-4486, miRNA-6850-5p, miRNA-642-3p, miRNA-7107-5p and miRNA-4281.…”
Section: Discussionmentioning
confidence: 99%
“…35) These highly expressed miRNAs included miR-4486, miR-6850-5p, miR-642b-3p, miR-7107-5p, and miR-4281 (Table 2). 35) 2. CNS infection and inflammation CSF/serum albumin ratio and CSF cell counts, culture, lactate and IgG or IgM measurements are basic CSF tests that have been used to diagnose infectious and inflammatory CNS disorders.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…Few studies have shown a relationship between seizures and CSF miRNA. Furthermore, febrile seizure patients displayed higher CSF exosomal miRNA profiles than controls, and these altered miRNA profiles appeared related to complex febrile seizures [ 35 ]. These highly expressed miRNAs included miR-4486, miR-6850-5p, miR-642b-3p, miR-7107-5p, and miR-4281 ( Table 1 ) [ 35 ].…”
Section: Csf Biomarkers Of Pediatric Neurological Disordersmentioning
confidence: 99%
“…Additionally, miR-4486 was significantly downregulated in patients with chronic obstructive pulmonary disease with eosinophilia and was an indicator of poor prognosis ( 15 ). Furthermore, increased expression of miR-4486 was found to be associated with febrile seizures ( 16 ). However, to the best of our knowledge, the expression and effect of miR-4486 in CC have not been previously reported.…”
Section: Introductionmentioning
confidence: 99%